THE EFFECT OF PRICE VALUE, HEDONIC MOTIVATION, HABIT, AND FOMO ON METAVERSE GAMES IN INDONESIA - Rahmat Hidayat; Vera Pujani; Hafiz Rahman; Ma’ruf (RADJA PUBLIKA, 2026)
The rapid and ongoing evolution of metaverse technology presents a dual-edged sword, offering both exciting new opportunities as well as significant challenges that pertain to its public adoption, particularly within the Indonesian context. This research endeavor aims to thoroughly investigate the various determinants that intentions to use of metaverse games technology among individuals in Indonesia. The theoretical framework underpinning this research is grounded in the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), which serves as a robust model for understanding technology acceptance. To achieve the objectives of this study, a quantitative research method was employed. This involved the distribution of offline and online questionnaires to a total sample of 324 participants. All participants were selected using purposive sampling techniques and had at least some level of awareness or prior experience with metaverse games technology. For the analysis phase, data processing utilized Structural Equation Modeling AMOS (SEM-AMOS) to validate hypotheses. The findings derived from this research indicate that key factors namely FOMO exert a significant influence on individuals intention to use metaverse games technology across Indonesian users.